Modernization OfGovernment Monitoring and Auditing Methods in The Event Of Applying the Privatization System in Iraq: An Applied Study in Iraq - Abdullah, LuayQays; SarhanAboud, Faisal; DuraidFarisKhayoon (International Journal of Psychosocial Rehabilitation, 2020)
This study deals with the problems and obstacles and finds solutions for them; in the case of the experience of the privatization system in some Iraqi government institutions and the conditions and requirements for modernizing government control methods in Iraq is to enable government oversight to preserve public money to avoid control gaps that occur as a result of the privatization of some Iraqi government institutions